Training and labour legislation : trends in recent legislation on vocational training - Barbagelata, Héctor-Hugo [Verfasser] (International Labour Office, 1997)
"Many industrial societies are undergoing a dynamic mutation caused mainly by technology, which propels them into the era of information and communications. Changes are so speedy and dramatic, and inevitably both so creative and destructive from a social point of view, that it is impossible to control them satisfactorily. It is for that reason that the transformation means a crisis for industrial legislation and relations systems - including social policies - as clearly shown by the growing 'fracture sociale'. The diversity and compexity of labour and training situations make this study by Professor Héctor-Hugo Barbagelata on education/vocational training legislation more than welcome. Of special importance is the author's survery of apprenticeship, in view of the growing need to establish links between school and enterprises. The study provides a complete and detailed picture of vocational training entitlements and bears witness once again to the juridical-labour tradition of Latin America." (Publisher, BIBB-Doku)
Formación y legislación del trabajo
Keywords: G 1.2 Arbeitsmarkt; G 2.3.4 Qualifikationswandel; G 1.2.3.2 Anforderungen & Bedarfe; I 2.3.3 Lateinamerika; Berufsbildungssystem; Reform; Arbeitsmarkt; Qualifikationswandel; Berufsbildungsrecht; Lateinamerika